Determinants of girls’ performance in science, mathematics and technology subjects in public secondary schools in Kenya - Musau, Lydia M.; Migosi, Joash A.; Muola, James M. (International Journal of Educational Administration and Policy Studies, 2013)
There has been incessant low academic performance in Science, Mathematics and Technology (SMT) subjects especially among girls at form four level in Kitui Central District over the years. The aim of this study was to investigate the determinants of girls’ performance in SMT subjects in public secondary schools. Using ex-post-facto survey research design, the study population covered all the six girls’ secondary schools in the district which also represented sample schools from which data was collected. Semi-structured questionnaires and document analysis sheets were used as instruments of data collection. The primary data collected was analysed by use of Statistical Package for Social Sciences (SPSS) version 17. Descriptive and inferential statistics were derived viz mean scores, percentages, correlation and regression coefficients. The Chi-square and one way ANOVA test statistics was used in hypothesis testing. Correlation and regression analysis were generated at 0.05 (2tailed) and 0.001(2-tailed) significance levels. The findings from the study explained why form four girls in Kitui County were not doing well in SMT subjects. The outcome of the study is expected to influence policy and decision-making on girls’ better performance in the subjects. Different approaches were recommended based on the findings to improve girls’ performance in SMT subjects.
Keywords: Determinants; Girls’ performance; Science; Mathematics; Technology; Public secondary schools; Kenya